APLIKASI MODEL HIDROGRAF SATUAN SINTETIS US SCS DALAM UPAYA OPTIMASI TATA GUNA LAHAN DAERAH ALIRAN SUNGAI MEMPAWAH KALIMANTAN BARAT - Wibowo, Hari (UNIVERSITAS LAMPUNG, 2010)
River discharge can be used as an indicator whether the catchment has an impact on the process control, especially in hydrology point of view. Beside, from that output the condition of the catchment can be evaluated. Information of river discharge will be more beneficial when it is presented as a hydrograph.Using synthetic unit hydrograph model, optimation of land use for catchment management planning can be computed. Optimal land use based on synthetic unit hydrograph model will support water resources conservation in Mempawah catchment. From the model result it is obtained that the largest land use in Mempawah catchment is for dry land with bush farming 64.4%, secondary swamp forest 12.8%, dry land farming 6.6%, swamp with bush 5.3%, secondary dry land forest 5.2%, bush 4.6%, open land 0.5%, settlement 0.4%, and embankment 0.2%. Average river discharge at the upstream is 17.54 m3/s, at the middle 59.05 m3/s and at the downstream 126.03 m3/s. At the current condition flood discharge (Qp) is 3,687.7323 cfs, time to peak (Tp) 81.2275 hours and base time 406.1376 hours. If the forest condition is worse then flood discharge becomes 1993.8815 cfs with Tp 150.2322 hours and Tb 406.1376 hours. For better forest condition flood discharge is 1559.7734 cfs, Tp 192.0441 hours and Tb 960.2207 hours. For good forest condition Qp is 1098.1439 cfs, Tp 272.7742 hours and Tb 1,363.8711 hours.